Nurses' autonomy and vulnerability in the Nursing Assistance Systematization practice - Menezes, Silvia Regina Tamae; Priel, Margareth Rose; Pereira, Luciane Lucio (Revista da Escola de Enfermagem da USP, 2011)
The objective of this study was to recognize the autonomy and vulnerability of nurses in the implementation of the Sistema da Assistência de Enfermagem (SAE) Nursing Care System through an integrative literature review, using content analysis. A survey was conducted, and 40 articles published between 1998 and 2008 were selected based on their relevance. Results showed two main categories of meaning: Benefits associated to the SAE practice (to patients, to the profession and to the institution) and Determinants for the Implementation of SAE (nurse's competence, training and education, record-instruments, infrastructure and collective sharing-construction). From the integration of the two categories, the highlights were the autonomy in acting with freedom and responsibility, science-based decision-making, and being valued for their social work, as well as the vulnerability expressed by interpersonal relationships, the wear generated by professional stress and the risk inherent to the service.